A multicentre randomized controlled trial of food supplement intervention for wasting children in Indonesia-study protocol - Aria Kekalih; Indriani Oka Anak Agung Sagung; Umi Fahmida; Evi Ermayani; Muchtaruddin Mansyur (BMC, 2019)
Abstract Background After the first six months of exclusive breastfeeding, children are introduced to liquids and semi-solid food, known as the complementary feeding phase. This phase is critical because it is often accompanied by improper feeding in children, which may lead to wasting and other nutrition problems. Fortified biscuits have been provided for wasting children as a nationwide programme. However, the ability of children to accept food supplementation remains questionable. This paper describes the protocol of a study investigating the efficacy of food supplementation (PMT biscuit) and nutrition education to improve the nutritional status of wasting children in Indonesia. Method The efficacy of a government food supplementation programme will be examined using a randomized control trial design. Parents with wasting children aged 6-17 months will be recruited to participate in the study. After obtaining informed consent and pre-intervention measures, participants will be assigned into three arms of intervention with PMT biscuits and/or nutrition education only. The two primary outcomes for this study are the nutritional status of wasting children and PMT biscuit compliance. Characteristics of all subjects in each arm will be analysed and compared with each other to assess their comparability at the beginning. The data will be collected at pre-intervention, at 3 months of intervention, post-intervention, and at the 6- to 9-month follow up. Discussion This paper aims to describe the study protocol of a randomized controlled trial investigating the effects of different PMT biscuit portion and nutrition education in two arms and nutrition education only in another arm. This study is important because it will provide evidence for the Indonesian government regarding the efficacy of food supplementation and/or food-based recommendations to improve the nutritional status of wasting children aged 6-23 months in Indonesia. Trial registration The study has been registered at clinicaltrials.gov, maintained by the National Library of Medicine (NLM) at the National Institutes of Health (NIH), on April 26, 2018, and was last updated on April 30, 2018 (registration number: NCT03509155).